Effectiveness of morphemic analysis of Graeco-Latin word parts as a vocabulary learning strategy among ESL learners - Norazha Paiman,; Ngee, Thai Yap; Mei, Yuit Chan (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2015)
This study examined the effects of morphemic analysis of Graeco-Latin roots and affixes as a vocabulary learning strategy among Malaysian ESL learners. Three intact classes of undergraduates majoring in health sciences were assigned to three different treatments which are instructions focussing on Graeco-Latin morphemic analysis, general morphemic analysis and use of contextual clues as vocabulary learning strategies. Participants in all groups underwent the instructional intervention which was done biweekly over a five-week period. Each group was taught how to derive word meanings using these three different strategies. A pre-test and post-test comprising three vocabulary tests measuring students’ morphemic analysis of general English words, morphemic analysis of Graeco-Latin word parts, and overall vocabulary size respectively, were administered. The scores were analysed using the paired sample T-test and one-way ANOVA to determine if there were improvements made in the three measures within each group, and subsequently whether the magnitude of improvement between the three groups were significant. The results indicated that (a) the group that were taught Graeco-Latin morphemic analysis scored the highest in all three vocabulary measures, (b) the group taught general morphemic analysis also improved in morphemic analysis of general English words but not Graeco-Latin words, and improved slightly in overall vocabulary size, but (c) the group that was taught to use contextual clues showed no improvement in all three vocabulary measures. The findings suggest that morphemic analysis, specifically analysis of Graeco-Latin word parts, may be a better vocabulary learning strategy particularly for the health sciences.